Evaluation of results of three and four-part fracture dislocations of proximal humerus in young adults using philos (proximal humerus internal locking system) - Thakur, Amit; Muzzafar, Khalid; Charak, Sumeet Singh; Dev, Bias; Ghani, Abdul (International Journal of Research in Medical Sciences, 2018)
Background: The fractures of proximal humerus constitute about 5% of fractures in adults third in number to fracture colles and hip usually in elderly patients due to a low energy trauma. In young patients the fractures are mostly due to high energy trauma and as such are associate with other soft tissue injuries. A sub group of young patients have a three or four fracture dislocation of shoulder joint. The aim of this study was to find the results of fixation by PHILOS in these young patients. Methods: This study was done in a teritiary referral centre over a period of about 1 year. All patients were operated within three weeks. Open fractures, patients with age more than 50 years were excluded from the study. All patients underwent open reduction and fixation using commercially available PHILOS. A minimum of 6 months follows up was essential for inclusion into the study. Final functional results were evaluated by Constant Murley scoring. Results: 14 patients were included in the study. The average age of patients was 38.42years. All fractures united. We had 71.4% excellent or good results. The complications noted were shoulder stiffness in 3, inadequate post op reduction, rotator cuff insufficiency, head necrosis, secondary osteo arthritis 1 each. Conclusions: Despite the relatively high rate of complications encountered in the management of these complicated high-energy fractures, the PHILOS plating system could be considered an adequate management of these patients.